Cognition and Translation Didactics - Riedemann Hall, Karin (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThe aim of this paper is to provide an overview of empirical research done with the same group of students during consecutive semesters of literary translation courses. We intend to change traditional translation didactics by using cognitive and pragmatic methods in order to optimize translation production and the student's self-correction awareness.